Current Status of Standardization of Traditional Chinese Medicine in China - Wang, Juan (Evid Based Complement Alternat Med, 2016)
As an important component of traditional medicine, Traditional Chinese Medicine (TCM) is widely spread and applied in more than 100 countries across the world. The standardization of TCM is very important for the international application of Chinese medicine. In this paper, we have explained and analyzed the standardization situations of TCM in China with the purpose of providing reference for standardization and international development of TCM.